The Political System of France After the 2024 Elections - Mladenović, Ivica (Political Life, 2025)
This paper analyzes the transformations of the French political system through the lens of structural changes in the political field, considering the institutions of the Fifth Republic not as fixed legal frameworks, but as a space of continuous struggle between actors seeking to preserve or redefine power relations. From Emmanuel Macron’s election in 2017 to the 2024 snap parliamentary elections, French politics has undergone a process of destabilization of established divisions and a reconfiguration of political cleavages, leading to a tripolarization of the political field and the disruption of the traditional functioning of power. The Fifth Republic, designed as a stable and efficient system, even at the cost of certain democratic achievements of liberal democracies, is now facing growing tensions between institutional structures and shifts in the balance of power within the political arena. The reliance on presidential authority has proven insufficient to manage the challenges posed by new political and social dynamics, while institutional rules are increasingly circumvented through crisis-driven decision-making mechanisms. This paper argues that these processes not only pose a challenge to the legitimacy of existing institutions, originally designed in a radically different socio-political context, but also necessitate a reassessment of institutional models that could offer solutions for overcoming the current crisis of the French political system.